Supply Chain Management in the Financial Markets - Sturc, B. J.; Pilch, C. N; Gurova, T. I (International Journal of Supply Chain Management, 2020)
Abstract- The article studies the phenomenon of supply chain management, which is most evident in financial markets along with other areas. Supply chain management has been attracting attention of researchers in relation to the explanation of the investment decision-making process in the financial markets. The article examines approaches to management from perspectives of different theories. Currently, the functioning of the financial markets has seen to become more complicated that hinders the technical analysis of the markets. Agents making decisions in the financial markets are more prone now to demonstrate massive behavior due to restricted information availability. It was revealed that supply chain management is most likely the underlying cause for bank crises and financial bubbles. It was found that management also leads to excess market volatility and mispriced stocks.